Efektivitas Simulasi Monsoonsim terhadap Pemahaman Perdagangan Internasional Pada Mahasiswa - Aisyah Nur Aulia; Egi Septiany Sunaryo; Meutia Gharsina Y.Z (Pusat Riset dan Inovasi Nasional, 2025)
This study evaluates the effectiveness of MonsoonSIM in enhancing the understanding of students in the International Trade Program for the ASEAN & China Region at Politeknik APP Jakarta regarding international trade concepts. A quantitative method was employed, using purposive sampling to select two student groups: Group A (semester 1), who had not used MonsoonSIM, and Group B (semester 3), who had experienced the use of MonsoonSIM. Data were collected through a quiz consisting of ten questions covering essential aspects of international trade, such as business management, supply chain, marketing, and demand forecasting. The results were analyzed using a paired t-test at a 5% significance level. The analysis revealed a t-value of 8.25, significantly exceeding the critical t-table value of 2.262, indicating a substantial improvement in students' understanding after using MonsoonSIM. Furthermore, semester 3 students demonstrated better comprehension compared to semester 1 students, confirming that MonsoonSIM effectively enhances not only theoretical understanding but also analytical and decision-making skills. This study concludes that MonsoonSIM is a superior simulation-based learning tool compared to traditional theoretical methods, making a vital contribution to the practical and applicable development of international trade education.